Ethical and Philosophical Consideration of the Dual-Use Dilemma in the Biological Sciences - Miller, Seumas (Springer, 2017)
The dual-use dilemma arises in the context of research in the biological and other sciences as a consequence of the fact that one and the same piece of scientific research sometimes has the potential to be used for harmful as well as good purposes. Discoveries that may lead to important advances in science and medicine might therefore also facilitate development of biological weapons of mass destruction. Scientists should be aware of the ways in which their well-intentioned research could be misused by others - and they should sometimes avoid research projects when the potential for harmful misuse is great. Policy makers must make tough choices about the extent to which the dual-use nature of research might justify increased oversight, regulation, and perhaps even censorship of science. This book examines the kinds of life-science experiments that give rise to the dual-use dilemma and provides philosophical analysis of the ethical issues and policy options surrounding dual-use research. Though the dual-use dilemma is an ethical issue, the vast majority of literature on the topic thus far has been written by scientists and security experts: this is the first book-length treatment of the topic by professional ethicists. It also challenges, and offers an alternative perspective to, the hugely influential U.S. National Research Council position on the dual-use dilemma.